Pergeseran Nilai-Nilai Budaya Bissu dalam Kehidupan Sosial di Kabupaten Bone - Supriadi (STAI DDI Kota Makassar, 2021)
Culture or culture is a tradition that is carried out by the community in an area that is still heavily influenced by its customs and is still being carried out until now which has developed and been passed down from generation to generation. Discussing about culture and culture in Indonesia, specifically in the province of South Sulawesi, it is known for its cultural diversity which is of course rooted in the diversity of values ​​that exist in its customary law community. The diversity of values ​​in the customary law community in South Sulawesi is a legacy of ancestors that has its own uniqueness compared to the culture owned by other regions, especially those in Bone Regency, which is related to the cultural values ​​of Bissu in the social life of the people in Bone Regency which still adhere to traditions and roles. as a preserver and preserver of classical Bugis cultural values ​​and is described as a demigod who has supernatural powers. The results showed that the background for the emergence of bissu in Bone Regency began when King Luwu was descended from the sky.